IMPROVING THE MECHANISM FOR MANAGING FINANCIAL RESOURCES OF LOCAL BUDGETS TO PROMOTE SOCIO-ECONOMIC DEVELOPMENT OF REGIONS IN UZBEKISTAN (American Journal of Business Management, Economics and Banking, 2024)
This article examines the mechanisms for enhancing the financial independence of local budgets to promote socio-economic development in Uzbekistan’s regions. In particular, it analyzes the policy of transferring at least 50% of personal income tax revenues and full property and land tax revenues from large taxpayers to regional and city budgets. The study highlights the positive impact of these mechanisms on local fiscal independence, investment activity, entrepreneurship, and infrastructure development. Empirical modeling using panel regression and a before–after approach demonstrates the effectiveness of these fiscal policies in strengthening local financial capacity and fostering balanced regional development.